Zur Biologie und Massenzucht der Getreidemotte Sitotroga cerealella Olivier. 1. Beitrag: Zur Eiablage von Sitotroga cerealella Olivier (Lepidoptera: Gelechiidae). - Schieferdecker, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The egg parasites of the genus Trichogramma used in biological pest control are bred mainly on eggs of Sitotroga cerealella Olivier. The particular conditions of the egging of the grain moth were studied with the purpose of developing a profitable mechanized mass breeding method with high productivity. The females lay their eggs preferably in chinks of a width of 0.17 to 0.22 mm. The yield of the eggs is 80 to 95 per cent with a density of 5 moths per cm2 bottom area of the vessels for eggs, and it drops to 50 per cent with a density of 20 moths per cm2, - The yield of the eggs is not influenced - or only negligibly so - by the presence or absence of folded pieces of cardboard used to collect the moths or by a paper pad soaked with starch. Additional feeding with honey water (1 part in 5) increases the egging in tests with individual pairs, but can at present hardly be used profitably in practical mass breeding. - Relations between body length, life span and egging of females are discussed. An influence of light on the quantity of eggs laid could not be established. At temperatures of 15°C to 32°C all developed eggs are laid. The greatest quantity of eggs is obtained with relative atmospheric moisture at about 75 per cent. - At 20°C the females lay most eggs on the third day after mating (40 per cent of the total, while the egging continues to the ninth day).